Sports and Gender Justice in Indonesia: Analyzing the Opportunities and Challenges for Women in Indonesian Sports (Indonesian Sports Justice Review, 2025)
Despite progress in gender equality in various sectors, women in Indonesian sports continue to face significant challenges, including limited access to resources, support, and media coverage. This paper examines the barriers that female athletes encounter in Indonesia, including institutional discrimination, societal expectations, and lack of adequate funding. It evaluates efforts to promote gender justice in sports, such as government policies, grassroots initiatives, and the role of female athletes in challenging stereotypes. The paper also discusses the broader societal impacts of promoting gender equality in sports, including the role of women in leadership positions and the visibility of women’s sports. Through case studies of successful female athletes and initiatives, this study proposes strategies to improve gender equality and create more equitable opportunities for women in Indonesian sports.